Metamorfoses da metamorfose humana: uma "pausa breve" no processo de identidade da pessoa em reabilitação motora por amputação - Smith, Maristela Pires da Cruz (2017)
The holistic view of man – man as a social being – suggests that rehabilitative actions, applied to patients with physical disablement – such as limbs amputation – evidence efficacy, resulting in improvement and faster readaptation of the person to new ways of “being part of the world”, even when experiencing the social stigma of being a “different person”. This study explored the epistemological presuppositions of the Critical Social Psychology, which were demonstrated through Music therapy techniques. It was expected that the practice of Music therapy sessions could facilitate the expression of the subject’s internal music, whose content was recorded by means of words, subsequently transformed into singing words and then into music composition. It embraced the joint participation of the persons involved in the clinical work, that is between the researcher (author of this project) and each patient, viewed individually, since it involved a participatory action research. The speech analysis of the narratives of the life stories was based on the categories that substantiated Critical Social Psychology in the study of man: activity, consciousness and affectivity – the category “identity” spans those cited – and interpreted using Music therapy techniques. The recordings entered were based on patients’ sonorous-musical behavior observations, applying the “Recording Model of Sonorous-Rhythmic-Musical, Body-Vocal and Behavioral Reactions” (Smith, 2002), not only for the objective registration, but also for the subjective musical interpretations, with “the identity as metamorphosis” being the main theoretical reference (Ciampa, 1977). The research is qualitative. The subjects were submitted to individual clinical processes in Music therapy, which sought to lead them to attribute new meaning to their worldview through the acquisition of new current characters, added to the past and with future and emancipatory life projects. “Giving meaning to the future and, retrospectively, to the past, translates into re-interpreting them”. In this way, the present could acquire meaning and have new possibilities (Ciampa, 1998, p.105). In this investigation, themes that involved “exclusion”, “inclusion” and “reinclusion” were also tackled, due to the fact that they are deemed to be issued of identity policies